Public provision of private goods and nondistortionary marginal tax rates: Some further results - Sören Blomquist; Vidar Christiansen; Luca Micheletto (Uppsala University, Department of Economics, 2009)
The incidence and efficiency losses of taxes have usually been analyzed in isolation from public expenditures. This negligence of the expenditure side may imply a serious misperception of the effects of marginal tax rates. The reason is that part of the marginal tax may in fact be a payment for publicly provided goods and reflects a cost that the consumers should bear in order to face the proper incentives. Hence, part of the marginal tax may serve the same role as a market price in the sense that it conveys information about a real social cost of working more hours. We develop this idea formally by studying an optimal income tax model in combination with a type of public provision scheme not analyzed before; the provision level is individualized and positively associated with the individual's labor supply. As examples we discuss child care, elderly care, primary education and health care. We show that there is a potential gain in efficiency where public provision of such services replaces market purchases. We also show that it is necessary for efficiency that, other things equal, marginal income tax rates are higher than in economies where the services are purchased in the market. This because the optimal tax should be designed so as to face the taxpayers with the real cost of providing the services. Hence, it might very well be that economies with higher marginal tax rates have less severe distortions than economies with lower marginal tax rates.
urn:nbn:se:uu:diva-108608
Keywords: H21; H42; I38; 330; Nonlinear income taxation; Marginal income tax rates; Public provision of private goods; In-kind transfers; Einkommensteuer; Grenzsteuersatz; Öffentliche Dienstleistung; Wohlfahrtsanalyse; Optimale Besteuerung; Sachtransfer; Kinderbetreuung; Theorie; Schweden